2000
DOI: 10.1034/j.1398-9995.2000.00495.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and immunologic effects of long‐term sublingual immunotherapy in asthmatic children sensitized to mites:a double‐blind, placebo‐controlled study

Abstract: Our results suggest that treatment for 2 years with SLIT is clinically safe and effective in significantly decreasing respiratory symptoms in children with mild to moderate asthma sensitized to HDM. On the other hand, the lack of changes of the immunologic parameters calls for further investigations with special reference to kinetics and mechanism(s) of action of this mode of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
181
3
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(196 citation statements)
references
References 28 publications
8
181
3
4
Order By: Relevance
“…It was reported that allergenspecific immunotherapy briefly increases the IgE level and subsequently reduces it. Fujimura et al reported that SLIT was more effective for JC pollinosis when the serum cedar allergen-specific IgG4/total IgE ratio was low before treatment than when the ratio was high [20]. In the present study, we found a significant increase of allergen-specific IgE after the pollen season in the SLIT group.…”
Section: Igg4/iggsupporting
confidence: 74%
See 1 more Smart Citation
“…It was reported that allergenspecific immunotherapy briefly increases the IgE level and subsequently reduces it. Fujimura et al reported that SLIT was more effective for JC pollinosis when the serum cedar allergen-specific IgG4/total IgE ratio was low before treatment than when the ratio was high [20]. In the present study, we found a significant increase of allergen-specific IgE after the pollen season in the SLIT group.…”
Section: Igg4/iggsupporting
confidence: 74%
“…Allergen-specific immunotherapy was reported to increase the blood level of IgG4, and Gleich proposed that allergen-specific IgG4 acts as a blocking antibody [18]. SLIT increases serum levels of antigen-specific IgG4 and also increases the antigen-specific IgG4/IgE ratio [19,20], and it has been suggested that serum IgG acts as blocking antibody and is associated with symptomatic improvement [21]. In Japan, it was reported that allergen-specific SLIT increases serum Cry j 1-specific IgG4 antibody in patients with JC pollinosis [22].…”
Section: Igg4/iggmentioning
confidence: 99%
“…The risk of bias was low in 3 studies. 22,32,34 Therefore, the strength of evidence is high that SLIT improves asthma symptoms, compared with placebo.…”
Section: Asthmamentioning
confidence: 99%
“…[22][23][24][32][33][34][35]37,38 Seven studies evaluated dust mite allergen. [22][23][24][32][33][34]38 The SLIT-treated children in the placebo-controlled studies demonstrated moderate to strong improvement in asthma symptoms. The risk of bias was low in 3 studies.…”
Section: Asthmamentioning
confidence: 99%
“…While the lack of allergen exposure for 12 months may have been responsible for the decrease of CADESI scores, it is important to note that it did not lead to a decrease of the allergen specific IgE, which remained in the positive range. Interestingly, other studies in humans have also reported clinical improvement in glycerin (vehicle) treated patients [33]. In one study on the effect of SLIT in children with mild to moderate asthma sensitized to DM a 30% improvement was reported in the control group after 12 months of treatment.…”
Section: Discussionmentioning
confidence: 87%